Population pharmacokinetics of tenofovir given as either tenofovir disoproxil fumarate or tenofovir alafenamide in an African population - Aida N. Kawuma; Roeland E. Wasmann; Phumla Sinxadi; Simiso M. Sokhela; Nomathemba Chandiwana; Willem D. F. Venter; Lubbe Wiesner; Gary Maartens; Paolo Denti (Wiley, 2023)
Abstract Tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF) are prodrugs of the nucleotide analogue tenofovir, which acts intracellularly to inhibit HIV replication. Whereas TDF converts to tenofovir in plasma and may cause kidney and bone toxicity, TAF mostly converts to tenofovir intracellularly, so it can be administered at lower doses. TAF leads to lower tenofovir plasma concentrations and lower toxicity, but there are limited data on its use in Africa. We used data from 41 South African adults living with HIV from the ADVANCE trial and described, with a joint model, the population pharmacokinetics of tenofovir given as TAF or TDF. The TDF was modeled to appear in plasma as tenofovir with a simple first‐order process. Instead, two parallel pathways were used for a TAF dose: an estimated 32.4% quickly appeared as tenofovir into the systemic circulation with first‐order absorption, whereas the rest was sequestered intracellularly and released into the systemic circulation as tenofovir slowly. Once in plasma (from either TAF or TDF), tenofovir disposition followed two‐compartment kinetics and had a clearance of 44.7 L/h (40.2-49.5), for a typical 70‐kg individual. This semimechanistic model describes the population pharmacokinetics of tenofovir when dosed as either TDF or TAF in an African population living with HIV and can be used as a tool for exposure prediction in patients, and to simulate alternative regimes to inform further clinical trials.